TRANSFORMASI KARAKTER MELALUI TATA RIAS DAN BUSANA PADA TOKOH YOUNG-SOOK DALAM FILM THE CALL (2020) - Idz Nada Zetra Aurora; Soekma Yeni Astuti; Ni Luh Ayu Sukmawati (MEDIAKOM, 2026)
Film The Call (2020) is South Korean fantasy thriller an adaptation of The Caller which was released in 2011. The appeal of the film in its ability to present an unexpected character transformation turns into an antagonist, Young-sook. This study uses a qualitative descriptive method with a film analysis approach to examine how visual elements are used to reinforce the character transformation of the antagonist. Data were collected through observation, focusing on the storyline that motivates the character to change their attitudes and behavior, based on Todorov’s three-act structure theory and Jeff Gerke’s character arc theory. Scenes from the film were captured and analyzed in depth to highlight changes in the makeup and costume aspects of the character. Research findings indicate that makeup and fashion serve not only as aesthetic elements but also play a significant role in creating character changes of the antagonist in reflecting the development of conflict in films.